Changes in bacterial number at different sites of oral cavity during perioperative oral care management in gastrointestinal cancer patients: preliminary study (Journal of Applied Oral Science, 2022)
Objective: The objective of this study was to clarify differences in bacterial accumulation between gastrointestinal cancer patients who underwent severely invasive surgery and those who underwent minimally invasive surgery. Material and Methods: We performed a preliminary investigation of gastrointestinal cancer patients who were treated at the Department of Surgery, Takarazuka Municipal Hospital, from 2015 to 2017 (n=71; 42 laparoscopic surgery, 29 open surgery) to determine changes in bacterial numbers at different sites of the oral cavity (tongue dorsum, gingiva of upper anterior teeth, palatoglossal arch), as well as mouth dryness and tongue coating indices. Specifically, patients received professional tooth cleaning (PTC), scaling, tongue cleaning, and self-care instruction regarding tooth brushing from a dental hygienist a day before the operation. Professional oral health care was also performed by a dental hygienist two and seven days after surgery. Oral bacteria numbers were determined using a bacterial counter with a dielectrophoretic impedance measurement method. Results: The number of bacteria at all three examined sites were significantly higher in the open surgery group when compared to the laparoscopic surgery group on the second postoperative day. Relevantly, bacterial count in samples from the gingiva of the upper anterior teeth remained greater seven days after the operation in patients who underwent open surgery. Furthermore, the dry mouth index level was higher in the open surgery group when compared to the laparoscopic surgery group on postoperative days 2 and 7. Conclusions: Even with regular oral health care, bacterial numbers remained high in the upper incisor tooth gingiva in gastrointestinal cancer patients who received open surgery. Additional procedures are likely needed to effectively reduce the number of bacteria in the gingival area associated with the upper anterior teeth